The Physical Tourist A Science Guide for the Traveler - Rigden, John S.; Stuewer, Roger H. (Birkhũser Basel, 2009)
Typical travel guides have sections on architecture, art, literature, music and cinema. Rarely are any science-related sites identified. For example, a current travel guide for Germany contains one tidbit on science: Einstein is identified as the most famous citizen of Ulm. By contrast, this travel guide walks a tourist through Berlin and identifies where Max Planck started the quantum revolution, where Einstein lived and gave his early talks on general relativity, and where, across the street, Einstein<U+0019>s books were burned by the Nazis. Or, if you are walking in Paris, this guide tells you where radioactivity was discovered and where radium was discovered. Scientific discoveries of the past, like art of the past, has shaped life in the 21st century. From this travel guide, a tourist will learn what other guides leave out.